The role of affective dimensions on tourist visit experience - Rashid, Basri (2013)
Tourists generally stored their visit experience as series of memories.These memories would have been evoked by various emotions as a result from encounters with numerous destinations features. Consequently it is proposed that emotional experience with destination’s elements is influential in determining tourist visit experience. In this case, tourist visit experience is signified by perceived visit value.This paper empirically analysed perceived visit value of international and domestic tourists at an Island Destination in Malaysia.Using questionnaire, a series of survey was conducted at the destination to gather information related to visitors’ demographic profiles, perceived performance of the destination features, as well as the affective condition of the tourist during their visit. Results of the analysis suggest that tourists initially evaluate their experience with the various elements of products and services at the destination.This would affect their emotional condition and eventually influences their perceived visit value level.Hence, it is concluded that effective dimension would be influential in determining tourist visit experience.The discussions in this paper are beneficial to various parties in the tourism and hospitality businesses in order to further understand tourist post visit experience.